Natural Biomaterials as Instructive Engineered Microenvironments That Direct Cellular Function in Peripheral Nerve Tissue Engineering - Powell, Rebecca; Eleftheriadou, Despoina; Kellaway, Simon; Phillips, James B. (Frontiers in Bioengineering and Biotechnology, 2021)
Nerve tissue function and regeneration depend on precise and well-synchronised spatial and temporal control of biological, physical, and chemotactic cues, which are provided by cellular components and the surrounding extracellular matrix. Therefore, natural biomaterials currently used in peripheral nerve tissue engineering are selected on the basis that they can act as instructive extracellular microenvironments. Despite emerging knowledge regarding cell-matrix interactions, the exact mechanisms through which these biomaterials alter the behaviour of the host and implanted cells, including neurons, Schwann cells and immune cells, remain largely unclear. Here, we review some of the physical processes by which natural biomaterials mimic the function of the extracellular matrix and regulate cellular behaviour. We also highlight some representative cases of controllable cell microenvironments developed by combining cell biology and tissue engineering principles.